2015
DOI: 10.1536/ihj.15-143
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Psychosocial Hazards and Arteriosclerosis

Abstract: SummaryThe association of psychosocial stress with cardiovascular disease (CVD) is still inconclusive. The aim of this study was to examine the relationships between arteriosclerosis and various work-related conditions among medical employees with various job titles.A total of 576 medical employees of a regional hospital in Taiwan with a mean age of 43 years and female gender dominance (85%) were enrolled. Arteriosclerosis was evaluated by brachial-ankle pulse wave velocity (baPWV). Workrelated conditions incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 42 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…By contrast, in societies with collectivistic values, such as Asia, high control would be perceived as a distressing lack of structure [ 69 ]. Therefore, it is not surprising to see that job control did not show any effect on arterial stiffness [ 15 , 18 ], or even that harmful effect was observed [ 14 ] in some Asian studies. In addition, the Job Demand–Control model was applied to measure work stress in most of the epidemiological studies on work stress and arterial stiffness/atherosclerosis mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, in societies with collectivistic values, such as Asia, high control would be perceived as a distressing lack of structure [ 69 ]. Therefore, it is not surprising to see that job control did not show any effect on arterial stiffness [ 15 , 18 ], or even that harmful effect was observed [ 14 ] in some Asian studies. In addition, the Job Demand–Control model was applied to measure work stress in most of the epidemiological studies on work stress and arterial stiffness/atherosclerosis mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, new findings also suggest arterial stiffness is tightly linked to cardiovascular disease [ 11 , 12 , 13 ]. To the best of our knowledge, six cross-sectional studies examined the potential associations between work stress and arterial stiffness, four from Japan [ 14 , 15 , 16 , 17 ], one from Taiwan [ 18 ] and one from The Netherlands [ 19 ]. Four of them found significant positive associations, i.e., higher work stress was related to increased arterial stiffness [ 15 , 16 , 17 , 19 ] whereas one study reported null findings [ 18 ]; and another study discovered significant negative associations [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We chose a baPWV because of its technical simplicity only requires attaching an easy-to-use blood pressure cuff onto foot and arms and accumulating evidence for usefulness. 11,13) Most previous studies employed the femoral and heart (hfPWV) 18) or carotid (cfPWV), a well-established index of central arterial stiffness. [19][20][21] The cfPWV measures stiffness from the aorta to iliofemoral axes, while baPWV reflects one in not only central elastic arteries but also peripheral muscular arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The PWV was calculated according to the previous literature. 13,15) Patients with an ankle-brachial index (ABI) < 0.9 were excluded from further evaluations. Measurement of cIMT: cIMT was measured by B-mode ultrasonography using a 5 MHz linear transducer (a10 color Doppler system, Aloka).…”
Section: Subjects and Biochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation